Sex hormones modulate brain damage in multiple sclerosis: MRI evidence. Issue 2 (14th January 2005) - Tomassini, V; Onesti, E; Mainero, C; Giugni, E; Paolillo, A; Salvetti, M; Nicoletti, F; Pozzilli, C
Abstract : Background: Sex related differences in the course and severity of multiple sclerosis (MS) could be mediated by the sex hormones. Objective: To investigate the relation between serum sex hormone concentrations and characteristics of tissue damage on conventional magnetic resonance imaging (MRI) in men and women suffering from relapsing-remitting MS. Results: Serum testosterone was significantly lower in women with MS than in controls. The lowest levels were found in women with a greater number of gadolinium enhancing lesions. A positive correlation was observed between testosterone concentrations and both tissue damage on MRI and clinical disability. In men, there was a positive correlation between oestradiol concentrations and brain damage. Conclusions: The hormone related modulation of pathological changes supports the hypothesis that sex hormones play a role in the inflammation, damage, and repair mechanisms typical of MS.